In Vitro Release of Metformin Hydrochloride from Sodium Alginate/Polyvinyl Alcohol Hydrogels - Guerrero-Nunez, J; Guerrero-Nunez, J; Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Martinez-Gomez, F (Elsevier Ltd, 2017)
Hydrogels, based on polysaccharides have found a number of applications as drug delivery carriers. In this work, hydrogels of full characterized sodium alginate (Mn 87,400 g/mol) and commercial poly(vinyl alcohol) (PVA) sensitive to pH and temperature stimuli were obtained using a simple, controlled, green, low cost method based on freeze-thaw cycles. Stable hydrogels of sodium alginate/PVA with 0.5:1.5 and 1.0:1.0 w/v concentrations showed very good swelling ratio values in distilled water (14 and 20 g/g, respectively). Encapsulation and release of metformin hydrochloride in hydrogels of 1.0:1.0 w/v sodium alginate/PVA was followed by UV spectroscopy. The hydrogel released a very low amount of metformin hydrochloride at pH 1.2; the highest release value (55%) was obtained after 6 h at pH 8.0. Also, the release of metformin hydrochloride was studied by 1H NMR spectroscopy, the temporal evolution of methyl group signals of metformin showed 30% of drug release after 3 h. © 2016 Elsevier Ltd